Resilience in Facing Ecological Challenges; Strategies for Integrating Environmental Education to Build Sustainable Behavior - Maghfiroh, Ana; Harmanto, Bambang; Simpol, Wanida; Devi, Putriana; Tarmusi, Riska Anisa (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
Ecological education in the form of green schools is a breakthrough program of UNESCO in order to. The purpose of this study are to 1) find out the implementation of the green school concept from two countries, namely indonesia and thailand. 2) to describe the impact of green schools to support sustainable behavior. In this study used descriptive quantitative research design. The subject in this study were the teacher of SMPN 2 Balong, Ponorogo, Indonesia and Ban-Ellert School Loei,Thailand, the school that have implemented the concept of green schools in both countries. The Researcher using focus group discussions as data collection. techniques,the data were analyzed used critical analysis.The results indicated of this study indicated that the implementation of the green school concept in both focused on environmental education and community involvement. The green school programmes has showed significant impacts on students’ ecological awareness and sustainable development.With green school program The students’ enjoyed the school environment and boosted their learning motivation. The active involvement of all parties, including teachers, students, parents, and the school community, are essential to succed this programme, efforts to integrate environmental values into the curriculum and day-to-day activities in schools also need to be enhanced to make the positive impact more visible.